Menguji Faktor-Faktor yang Mempengaruhi Niat Pembelian Ulang Secara Online - Pribanus Wantara; Siti Anugrahini Irawati (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
There has been a surge in online shopping in Indonesia in recent years. More and more customers are starting to shop online as they develop trust in online transactions. This growth makes online businesses appear profitable and therefore attracts new and tougher competition. Therefore, getting customers has become a big challenge, even more difficult is retaining customers for repeat purchases. Repurchase is critical for b usiness growth and continuity in today's com petitive scenario. Therefore, the purpose of this study is to exam ine the influence of factors such as electronic trust, electronic satisfaction on electronic loyalty and electronic repurchase intention in online shopping. The results of this study are: e- satisfaction partially affects e-loyalty, e-trust and e-repurchase intention; e-trust partially affects e-loyalty, and e-repurchase intention; and e-loyalty partially affects e-repurchase intention.